The Role of Human Capital in Regional Economic Growth: Evidence from Central Java- Indonesia - Andini Kusumawardhani (Niqosiya: Journal of Economics and Business Research, 2025)
Human Capital is one of the most powerful support factors for economic performance of a region. Central Java is one of provinces in Indonesia that has high quality human resources with a high Human Development Index (HDI). Programs to improve the quality of human resources in Central Java province need to be encouraged to further support national growth and economic equality for all people. This study uses multiple linear regression using panel data to analyze the simultaneous relationship between several indicators of human capital to economic growth more comprehensively and measure the effect of each independent variable on district/city economic growth of 35 cities and regencies in Central Java Province during 2011 - 2024 period. These findings robustly support endogenous growth theory, that human capital indicators represented by education (expected years of schooling, education expenditure, and literacy) and health (health facilities and life expectancy) have a positive and significant effect on regional economic growth. These results highlight the pivotal role of human capital in enhancing GRDP per capita and support the endogenous growth theory, which emphasizes the importance of internal factors such as knowledge and health in sustaining long-term economic development. As such, regional development policies should prioritize strategic investments in education and healthcare to strengthen human capital and promote inclusive and sustainable growth.